2D Resistivity Imaging of an oil spill site at Koya town, Iraq-Kurdistan Region - Aziz, Bakhtiar; Ahmad, Omar; Ali, Peshawa (Iraqi Journal of Science, 2024)
An oil spillage has been a great threat to human life in parts of Koya district, especially through the contamination of domestic water. An attempt was made to find and map the extent of pollution in the area. According to a field survey, more than 17 springs and 34 hand-dug and artesian wells have been contaminated with crude oil. The contamination was recorded recently after loading began of tens of oil tankers in the Taq-Taq oil field, and as a result hundred barrels of oil have spilled into the creeks and soil daily. Hence, 2D resistivity imaging was adopted via four laid-out traverses running normal to the strike of the outcrops. A Wenner-Schlumberger array configuration was used to achieve both vertical and lateral resistivity distributions for the investigated site; profiles were surveyed using 5-metre electrode spacing. The interpretation shows that after one year, contamination anomalies of high resistivity represent the locations of contaminated zones, and the migration of the spilled oil is detected within the dry sandstone of the Enjana (Upper Fars) Formation. So, there is contamination by crude oil of the sandstone above the water table, and after one year this has led to a decrease in conductivity of the contaminated zone owing to the absence of natural bioactivity. The migration paths of the crude oil beneath the subsurface were mapped and were found within the sandstone and siltstone layers, trending NW-SE.